Highly variable breeding phenology in an arid region colonial cooperative breeder, the Sociable Weaver Philetairus socius - (:unkn) unknown (My University, 2024)
Describing breeding phenology (the timings of reproductive events) is central for studying individual fitness and population dynamics. While fundamental differences in breeding strategies between different biomes (e.g. tropics and temperate regions) have long been identified, detailed descriptions based on long-term studies of individually marked birds are biased towards the bird populations in North America and Europe. As a result, crucial information on bird breeding phenology remains scarce in bird diversity hotspots such as southern Africa, an area that is also highly threatened by climate change. In most arid regions of the Southern Hemisphere, especially in southern Africa and Australia, rainfall patterns are often erratic, leading to variation in the duration of the conditions suitable for breeding within and between years. These dynamic environmental conditions select for flexible and opportunistic breeding strategies. Consequently, breeding seasons vary from year to year in both length and intensity — from skipping breeding to prolonged breeding with multiple attempts per pair. Here, we report on the highly variable breeding cycle of the Sociable Weaver Philetairus socius, a colonial cooperatively breeding passerine from the arid savannahs of the Kalahari region of southern Africa. We monitored the reproduction of an individually marked population over 11 years. Breeding activity usually started at the end of winter, but varied greatly in the starting date as well as duration (from 4 to 11 months). The percentage of active nests also changed greatly within and between seasons. As a result, the number of clutches laid annually per female varied markedly between years, with some extreme cases, such as a single female that laid 8 clutches in a year, and others suspected to lay up to 13 clutches, which is one of the highest numbers reported for wild bird species.
Keywords: African Research